Family Planning and Christianity: A Pastor's View Between the Commandment of Genesis 1:28 and the Implementation of Family Planning For Churches in Indonesia - Hutabarat, Patuan Andre; Harianja, Simion Diparuma; Samosir, Lustani (the International Journal of Education, Theology, and Humanities, 2023)
This research is motivated by the fact that there is an explosion of population growth in the world, which causes environmental issues / natural destruction and impacts the lives of mankind. This contradicts the original creation of mankind (Gen 1:28), where God the Creator had created mankind in his image, blessed them to be fruitful, subdued the earth, and cared for allcreation. However, because mankind wanted to be like God, they fell into sin, and God punished them, which resulted in mankind's responsibility to care for the earth becomingdestructive to the world and nature due to a lack of self-control. Seeing the destruction of nature and the vast population growth, humans began to control themselves through the family planning movement to curb the population growth rate.This research uses qualitative research with data collection techniques in the form of literature and field studies consisting of moderate participatory observation, semi-structured in-depth interviews, and documentation studies; the research instrument is the researcher himself, with 6 informants determined based on snowball techniques and triangulation analysis. The results show that the effectiveness of the role of pastors/churches is instrumental in forming a responsible family through premarital counseling for those who will start/create a new family.